DYEING MACHINE MAINTENANCE PLANNING USING THE FAILURE MODE AND EFFECT ANALYSIS (FMEA) METHOD AT PT BOO YOUNG INDONESIA CIKANDE – SERANG - Yosep Muhammad Syahid; Naufal Affandi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2021)
PT. Boo Young Indonesia is a company that manufactures shoelaces for famousbrands such as Adidas, Nike, Puma, Under Armour. Based on the findings obtained by the researchers from the Observation Results there is a frequent engine damage to the Dyeing Machine.The damage resulted in the company experiencing a failure in the production process resulting in the company experiencing losses. The analysis of this study aims to determine the application of the Failure Mode Effect And Analysis (FMEA) method can provide optimal scheduling results in the treatment of the dyeing machine so that damage to the machine can be prevented and reduced so that there is no downtime on the dyeing machine